Testing the fidelity of thermometers at ultrahigh temperatures. (8th May 2019) - Clark, Chris; Taylor, Richard J. M.; Johnson, Tim E.; Harley, Simon L.; Fitzsimons, Ian C. W.; Oliver, Liam
Abstract: A highly residual granulite facies rock (sample RG07‐21) from Lunnyj Island in the Rauer Group, East Antarctica, presents an opportunity to compare different approaches to constraining peak temperature in high‐grade metamorphic rocks. Sample RG07‐21 is a coarse‐grained pelitic migmatite composed of abundant garnet and orthopyroxene along with quartz, biotite, cordierite, and plagioclase with accessory rutile, ilmenite, zircon, and monazite. The inferred sequence of mineral growth is consistent with a clockwise pressure–temperature ( P – T ) evolution when compared with a forward model ( P – T pseudosection) for the whole‐rock chemical composition. Peak metamorphic conditions are estimated at 9 ± 0.5 kbar and 910 ± 50°C based on conventional Al‐in‐orthopyroxene thermobarometry, Zr‐in‐rutile thermometry, and calculated compositional isopleths. U–Pb ages from zircon rims and neocrystallized monazite grains yield ages of c. 514 Ma, suggesting that crystallization of both minerals occurred towards the end of the youngest pervasive metamorphic episode in the region known as the Prydz Tectonic Event. The rare earth element compositions of zircon and garnet are consistent with equilibrium growth of these minerals in the presence of melt. When comparing the thermometry methods used in this study, it is apparent that the Al‐in‐orthopyroxene thermobarometer provides the most reliable estimate of peak conditions. There is a strong textural correlation between the temperatures obtained using the Zr‐in‐rutile thermometer––maximum temperatures are recorded by a single rutile grain included within orthopyroxene, whereas other grains included in garnet, orthopyroxene, quartz, and biotite yield a range of temperatures down to 820°C. Ti‐in‐zircon thermometry returns significantly lower temperature estimates of 678–841°C. Estimates at the upper end of this range are consistent with growth of zircon from crystallizing melt at temperatures close to the elevated (H 2 O undersaturated) solidus. Those estimates, significantly lower than the calculated temperature of this residual solidus, may reflect isolation of rutile from the effective equilibration volume leading to an activity of TiO2 that is lower than the assumed value of unity.